Implications of Taxation Cluster for the Improvement of Indonesian Economy in the Perspective of Omnibus Law - Saputra, Tri Eka (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
The focus of the study in this article is the existence of a taxation cluster in the copyright law with its formation using the omnibus law method. The use of the omnibus law method has the potential to overcome overlapping regulations, efficiency of regulatory changes, and overcome sectoral ego in legislation. This can be seen in the taxation cluster in the employment copyright law with several changes occurring in it. Despite public opinion about tax collection, the taxation cluster arrangement in the copyright law can have a positive impact on economic improvement through dividend tax exemptions and tax incentives for publicly listed companies. This article aims to answer the impact of the copyright law in improving the economy in Indonesia, as well as the implications of the taxation cluster in the omnibus law as an improvement in the Indonesian economy. The results of this study indicate that: The Taxation Cluster in the copyright law is a strategic step by the Government of Indonesia to improve the country’s economy. The taxation cluster changes in the law aim to strengthen the economic and financial sectors by simplifying tax regulations, encouraging investment, reducing the tax burden, and addressing investment barriers. Overall, the tax arrangements in the job creation law have great potential to drive economic growth, support national development, and strengthen Indonesia’s economic position if implemented effectively. ___ References Books with an author: Falak, Y. (2020). Sektor Perpajakan dalam UU Cipta Kerja: Perubahan Komprehensif untuk Kemudahan Berusaha; Di Balik Undang-Undang Cipta Kerja. Jakarta: Badan Kebijakan Fiskal-Kementerian Keuangan RI. Marzuki, P. M. (2005). Penelitian Hukum. Jakarta: Kencana Prenada. Pohan, C.A. (2018). Manajemen Perpajakan : Strategi Perencanaan Pajak dan Bisnis. Jakarta: PT Gramedia Pustaka Utama. Suska. (2020). Mendukung Kemudahan Berusaha Melalui Penyesuaian Aturan PPN dalam Undang-Undang Cipta Kerja, (Di Balik Undang-Undang Cipta Kerja). Jakarta: Badan Kebijakan Fiskal-Kementerian Keuangan RI. Journal articles: Adiwijaya, A. J. S., Suryani, D., Komandoko, K., & Vijay, M. (2022). Urgensi Reformasi Undang-Undang tentang Pembentukan Peraturan Perundang-undangan sebagai Dampak Penerapan Konsep Omnibus Law di Indonesia. Jurnal Ilmiah Living Law, 14(2), 117-128. Aji, A. S., Setiono, J., & Santoso, B. (2022). Juridical Review of the Principles and Systems of Collecting Local Taxes in National Development. International Journal of Law and Politics Studies, 4(2), 51-58. Arham, S., & Saleh, A. (2019). Omnibus Law Dalam Perspektif Hukum Indonesia. Petitum, 7(2), 72-81. Asnawi, M. I. (2016). Implikasi Pengelolaan BUMN Persero dalam Kerangka Welfare State berdasarkan Mekanisme Perseroan Terbatas. Jurnal Hukum Samudra Keadilan, 11(1), 126-144. Faisol, I. A., & Rahmawati, E. (2022). Analisis Persepsi Wajib Pajak dan Implementasi Undang-Undang Cipta Kerja Segmen Kemudahan Berusaha Bidang Perpajakan. InFestasi, 18(1), 76-87. Hamidi, J. (2011). Paradigma Baru Pembentukan dan Analisis Peraturan Daerah (Studi atas Perda Pelayanan Publik dan Perda Keterbukaan Informasi Publik). Jurnal Hukum Ius Quia Iustum, 18(3), 336-362. Handayani, T., & Abubakar, L. (2017). Perkembangan Hukum Sektor Jasa Keuangan Dalam Upaya Percepatan Pertumbuhan Ekonomi Nasional. DE LEGA LATA: Jurnal Ilmu Hukum, 2(2), 418-444. Harjono, D. K. (2020). Konsep Omnibus Law Ditinjau dari Undang Undang No. 12 Tahun 2011 tentang Pembentukan Peraturan Perundang Undangan. Jurnal Hukum To-ra, 6(2), 96-110. Lala, A., & Sudiharto, S. (2021). Urgency of the Omnibus Law Bill. Journal “Omnibus Law Opportunities and Challenges Towards Entrepreneurs and Labor: Comparative Review”, 1(1),77-84. Prabowo, A. S., Triputra, A. N., Junaidi, Y., & Purwoleksono, D. E. (2020). Politik Hukum Omnibus Law di Indonesia. Jurnal Pamator: Jurnal Ilmiah Universitas Trunojoyo, 13(1), 1-6. Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163. Rahman, M. S. (2018). Makna Filosofis Rechtstaat dalam Konteks Kebijakan Pembangunan Hukum di Indonesia. Meraja Journal, 1(2), 40-45. Ricky, R. (2023). Pengenaan Pajak Penghasilan Terhadap Warga Negara Asing yang Menjadi Wajib Pajak Dalam Negeri. Locus Journal of Academic Literature Review, 2(2), 126-144. Susdarwono, E. T., & Rizal, M. S. (2021). Praktik Omnibuslaw di Indonesia dilihat dari Segi Pembangunan Hukum Ekonomi. Journal of Law and Policy Transformation, 6(1), 90-100. Tresnajaya, R. T. J. (2021). Analisis Perubahan Ketentuan Subjek Pajak Orang Pribadi Pada Undang-Undang Cipta Kerja Terhadap Pajak Penghasilan Orang Pribadi dan Mobilitas Sumber Daya Manusia. Jurnal Pajak dan Keuangan Negara (PKN), 3(1), 98-111. Utomo, P. (2020). Omnibus Law: Dalam Perspektif Hukum Responsif. Nurani Hukum, 2(1), 33-41. Wijaya, S., & Sabina, D. I. A. (2021). Reformulasi Pengkreditan Pajak Masukan Pasca Omnibus Law. Jurnal Pajak Indonesia (Indonesian Tax Review), 5(1), 1-19. Yusliwidaka, A. (2022). Menakar Efektivitas Konsep Omnibus Law Dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja di Masa Pandemi Covid-19. Jurnal Hukum Progresif, 10(2), 167-178.